Equilibrium 4

3 A (g) + 2 B (g) <-> 4 C (g) Keq=3.0
2B (g) + 2E (g) <-> 4 D (g) + 2A (g) Keq= 0.5
 
Determine the equilibrium constant, Keq, for the following reaction using the information provided above. 
5A (g) + 4D (g) <-> 4C (g) + 2E (g)

First try to get the final net equation 5A (g) + 4D (g) <-> 4C (g) + 2E (g) from the given equations 
take equation 1 as such and reverse eq 2 

3 A (g) + 2 B (g) <-> 4 C (g) K1=3.0
 4 D (g) + 2A (g)<---->2B (g) + 2E (g) K2= 1/0.5
Add the equations and multiply K1 with K2 to get Keq for the net reaction.